1981
DOI: 10.1111/j.1476-5381.1981.tb09130.x
|View full text |Cite
|
Sign up to set email alerts
|

Exocytotic Secretion of Catecholamines From the Cat Adrenal Medulla by Sodium Deprivation: Involvement of Calcium Influx Mechanism

Abstract: Cat adrenal glands were perfused with Ca‐deficient medium and secretion of catecholamines (CA) was induced by perfusion with Na‐free medium in which NaCl was replaced by an osmotically equivalent amount of sucrose. Release of CA and dopamine‐β‐hydroxylase (DBH), but not that of phenylethanolamine‐N‐methyltransferase, was concomitantly found in the effluents when the adrenals were stimulated, indicating that secretion was due to exocytosis. Secretion of CA induced by Na‐free (sucrose) medium was dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…The rate of 45Ca efflux from the medullary slices (RINK, 1977) and the perfused cortex-free medulla (AGUIRRE et a!., 1977) was largely dependent on external Na. Conversely, all the procedures leading to a rise in the concentration of internal Na was found to increase Ca influx in exchange for internal Na (that is, Na-dependent Ca influx) thereby increasing catecholamine (CA) secretion (ESQUERRO et al, 1980;GARCIA et al, 1980GARCIA et al, , 1981bNISHIMURA et al, 1981;SORIMACHI et al, 1981;SORIMACHI and YAMAGAMI, 1983). Recently, GARCIA et al (1981a) reported that ouabain treatment of the adrenal gland enabled a small increment of external K to increase markedly the rate of CA secretion.…”
mentioning
confidence: 99%
“…The rate of 45Ca efflux from the medullary slices (RINK, 1977) and the perfused cortex-free medulla (AGUIRRE et a!., 1977) was largely dependent on external Na. Conversely, all the procedures leading to a rise in the concentration of internal Na was found to increase Ca influx in exchange for internal Na (that is, Na-dependent Ca influx) thereby increasing catecholamine (CA) secretion (ESQUERRO et al, 1980;GARCIA et al, 1980GARCIA et al, , 1981bNISHIMURA et al, 1981;SORIMACHI et al, 1981;SORIMACHI and YAMAGAMI, 1983). Recently, GARCIA et al (1981a) reported that ouabain treatment of the adrenal gland enabled a small increment of external K to increase markedly the rate of CA secretion.…”
mentioning
confidence: 99%
“…This Na-Ca exchange system might be involved in the control of the intracellular concentration of ionized Ca levels and, therefore, in the modulation of catecholamine release by chromaffin cells. Procedures leading to an increase in the ratio [Na]i/[Na]l such as Na deprivation or ouabain treatment, will activate this system favouring the entry of Ca into the cell, in exchange for internal Na Nishimura et al, 1981;. Then the elevated intracellular [Ca] will result in a parallel increase of catecholamine output by the gland.…”
Section: Perfusion Mediamentioning
confidence: 99%
“…The response was reversibly diminished 10 min after exposure to a medium containing 5 mM K. These results are essentially similar to those obtained in the chromaffin cells, where all the procedures leading to an expected rise in internal Na increased catecholamine secretion in response to Ca reintroduction (ESQUERRO et al, 1980;GARCIA et al, 1981;SORIMACHI et al, 1981). We have therefore tested the effects of D 600 (methoxyverapamil) and Co ions on the responses to Ca after ouabain treatment, since catecholamine secretion in response to Ca reintroduction with or without simultaneous removal of external Na was sensitive to these Ca channel blockers in the chromaffin cells (AGUIRRE et al, 1979;NISHIMURA et al, 1981;Fig. 2.…”
mentioning
confidence: 95%